(untitled) (ModaPalavra e-periódico, 2025)
Representation is crucial in both social issues and fashion, espe-cially when it comes to real bodies. This research aimed to analyze how the representation of plus-size women is portrayed in Man-equim magazine in the 1990s and today. For this, four editions of the magazine were selected that presented changes in their mea-surement tables, two editions corresponding to the years 1991 and 1996 and two editions from the year 2022. The methodology ap-plied was based on a bibliographical review and analysis content centered on measurement tables, templates and interpretation of the editions mentioned. The methodology applied was based on an in-depth literature review, encompassing books and articles, as well as a detailed analysis of the four measurement charts from the mentioned issues. It was possible to observe that, in the 1990s, there was a brief period of improvement in the representation of plus-size women in the magazine. However, over the years, much has been discussed about representation, but little has been done to meet consumer demands. The results indicate that, although there is an intention to include plus-size women in Manequim mag-azine, this inclusion occurs in the texts but is not reflected in the measurement charts. This shows a discrepancy between discourse and practice, highlighting that representation is still a challenge to be overcome in the fashion field.